SOME SUBSTANDARD APPLICATIONS OF THE COSINES THEOREM - Федак, Іван Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Some substandard methods of Olympiad problems solutions with help of the cosines theorem have considered.